A high-throughput genomic tool: diversity array technology complementary for rice genotyping - Xie, Yong; McNally, Kenneth; Li, Cheng-Yun; Leung, Hei; Zhu, Youyong (Wiley, 2006)
Diversity array technology (DArTTM) was a genotyping tool characterized gel‐independent and high throughput. The main purpose of present study is to validate DArT for rice (Oryza sativa L.)genotyping in a high throughput manner. Technically, the main objective was to generate a rice general purpose gene pool, and optimize this genomic tool in order to evaluate rice germplasm genetic diversity. To achieve this, firstly, a general‐purpose DArT array was developed. Ten representatives from 24 varieties were hybridized with the general‐purpose array to determine the informativeness of the clones printed on the array. The informative 1 152 clones were re‐arrayed on a slide and used to fingerprint 17 of 24 germplasms. Hybridizing targets prepared from the germplasm to be assayed to the DNA array gave DNA fingerprints of germplasms. Raw data were normalized and transformed into binary data, which were then analyzed by using NTSYSpc (Numerical taxonomy system for cluster and ordination analysis, v. 2.02j) software package. The graphically displayed dendrogram derived from the array experimental data was matched with simple sequence repeats genotyping outline and varieties' pedigree deviation of the different varieties. Considering DArT is a sequence‐independent genotyping approach, it will be applied in studies of the genetic diversity and the gene mapping of diverse of organisms, especially for those crops with less‐developed molecular markers.(Managing editor: Ya‐Qin Han)